Determination of Clinical Outcomes by Proximal Row Carpectomy (PRC) Combined with Interposition Arthroplasty Using the Dorsal Capsule and Acellular Dermal Matrix (ADM) - Yoo, Jae-Sung (Medical Research and Its Applications Vol. 9, 2024)
Background: Proximal row carpectomy (PRC) has been used extensively and has demonstrated good long-term results in cases of wrist arthritis. Its use is restricted, though, if arthritis affects the capitate or lunate fossa. To overcome these constraints, new surgical techniques that incorporate multiple interposition arthroplasty techniques have been developed recently. Aim: This present study aimed to perform PRC combined with interposition arthroplasty using the dorsal capsule and acellular dermal matrix (ADM), and to analyze the clinical outcomes of these procedures. Methods: The study encompassed patients diagnosed with stage 3 or 4 scapholunate advanced collapse, stage 2 or 3 scaphoid nonunion advanced collapse, and individuals exhibiting arthritis progression in the capitate head or lunate facet. Fourteen cases that underwent PRC and interposition arthroplasty with ADM were retrospectively reviewed. The researchers evaluated the patients' Visual Analog Scale (VAS) pain scores, Disabilities of the Arm, Shoulder, and Hand (DASH) scores, range of motion (ROM), retear incidence, and radiocarpal distance (RCD). Results: One-year post-surgery, the VAS pain scores, DASH scores, and ROM all showed statistically significant improvement compared to pre-surgery levels. The radiological results indicated that the postoperative mean RCD was 4.8 ± 0.8 mm, while the one-year follow-up mean RCD was 3.6 ± 0.5 mm. Additionally, there was no observed failure of the allodermis graft in any of the cases at the one-year follow-up. Four-corner arthrodesis may be considered for application in SNAC SLAC stages; however, it exhibits a higher complication rate and revision rate compared to PRC. Moreover, it poses limitations in cases of pre-existing radiolunate articular degeneration, making its application challenging in such scenarios. Conclusion: The PRC and interposition arthroplasty with ADM demonstrated significantly improved clinical outcomes after surgery, effectively maintaining RCD without graft failure.